2004
DOI: 10.1159/000079053
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the SF-36 Questionnaire in Patients on the Waiting List for a Kidney Transplant and Transplant Patients

Abstract: Background/Aims: The aim of this study is to explore the validity and reliability of the health-related quality of life SF-36 questionnaire in patients undergoing renal replacement therapy. Methods: A multicenter descriptive transversal study was carried out in Galicia, Spain, with patients undergoing renal replacement therapy. The tool used to measure the health-related quality of life was the authorized Spanish version of the ‘SF-36’ generic health questionnaire. The internal consistency of this survey was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 15 publications
(21 reference statements)
2
32
0
2
Order By: Relevance
“…(5). The mean physical functioning score that was reported in a study of patients in Spain was higher (74.2 Ϯ 24.0), but that mean was derived from scores of 72 patients with a functioning transplant as well as scores of 213 patients who were on the waiting list for a kidney transplant (8). Our study indicated that a higher level of physical functioning reported near the start of ESRD treatment was associated with reduced risk for a "bad event," i.e., hospital readmission, graft loss, and death, in the period after kidney transplantation.…”
Section: Discussionmentioning
confidence: 92%
“…(5). The mean physical functioning score that was reported in a study of patients in Spain was higher (74.2 Ϯ 24.0), but that mean was derived from scores of 72 patients with a functioning transplant as well as scores of 213 patients who were on the waiting list for a kidney transplant (8). Our study indicated that a higher level of physical functioning reported near the start of ESRD treatment was associated with reduced risk for a "bad event," i.e., hospital readmission, graft loss, and death, in the period after kidney transplantation.…”
Section: Discussionmentioning
confidence: 92%
“…This scale was then categorized into tertiles: scores 0–30 (fair and poor) were categorized as ‘poor health’; 31–60 (good) as ‘average health’, and 61–100 (excellent and very good) as ‘excellent health’ [15]. The validity and reliability of the first item of the SF-36 has been confirmed in patients with renal disease, including those after KT [16,17,18]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, an indirect assessment of muscle mass can be performed via muscle strength, i.e. by using hand-grip test, or via subjective evaluation of the daily routine activities, as reported in specific questions of the SF-36 questionnaire [17].…”
Section: Introductionmentioning
confidence: 99%